2017
DOI: 10.15537/smj.2017.2.15649
|View full text |Cite
|
Sign up to set email alerts
|

The serum levels of tumor marker CA19-9, CEA, CA72-4, and NSE in type 2 diabetes without malignancy and the relations to the metabolic control

Abstract: Objectives:To investigate whether there is a difference in carbohydrate antigen 19-9 (CA19-9), carcinoembryonic antigen (CEA), carbohydrate antigen 72-4 (CA72-4), and neuron-specific enolase (NSE) between diabetic and non-diabetic patients.Methods:A retrospective analysis was performed in 268 type 2 diabetic patients and 95 non-diabetic ones, and their serum levels of CA19-9, CEA, CA72-4, and NSE were compared in our endocrine ward at the Tianjin Fourth Central Hospital, Tianjin, China during the period from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 12 publications
3
30
0
Order By: Relevance
“…Litvak et al followed patients who underwent resection for locoregional colorectal cancer and reported that false‐positive or transient elevations of CEA are common in the range of 5 to 15 ng/mL; however, the authors did not reveal the specific cause of this transient elevation. Although false elevation of CEA associated with diabetes has been noted, the relationship between the extent of change in glycemic control status and CEA level had not been demonstrated before this study. Therefore, it is noteworthy that the follow‐up level of CEA significantly decreased as HbA1c decreased with glycemic control, demonstrating the assumed effect of glycemic control on CEA levels, although this conclusion was based on data from a small number of follow‐up subjects.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Litvak et al followed patients who underwent resection for locoregional colorectal cancer and reported that false‐positive or transient elevations of CEA are common in the range of 5 to 15 ng/mL; however, the authors did not reveal the specific cause of this transient elevation. Although false elevation of CEA associated with diabetes has been noted, the relationship between the extent of change in glycemic control status and CEA level had not been demonstrated before this study. Therefore, it is noteworthy that the follow‐up level of CEA significantly decreased as HbA1c decreased with glycemic control, demonstrating the assumed effect of glycemic control on CEA levels, although this conclusion was based on data from a small number of follow‐up subjects.…”
Section: Discussionmentioning
confidence: 57%
“…Litvak et al followed patients who underwent resection for locoregional colorectal cancer and reported that false-positive or transient elevations of CEA are common in the range of 5 to 15 ng/mL; 36 however, the authors did not reveal the specific cause of this transient elevation. Although false elevation of CEA associated with diabetes has been noted, 9,13,14 There are some limitations of this study. First, we could not perform an experiment to elucidate the clear mechanism connecting diabetes or increased HbA1c to CEA levels.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The level of CA 19-9 has been explored in various studies; it was increased in patients with type 2 diabetes and highly correlated with glycemic control [ 18 20 ]. CEA has also been reported to be associated with hyperglycemia in patients with diabetes in small-scale studies [ 19 , 20 ]. However, the influence of glycemic control on the levels of CEA was scarcely investigated in large-scale samples.…”
Section: Introductionmentioning
confidence: 99%
“…A higher level of CA19‐9 has often been used as a clinical tumor marker of pancreatic cancer. Elevated serum CA19‐9 levels were observed not only in malignant tumors, but also in patients with inflammatory conditions, including pancreatitis and diabetes mellitus. A positive association between high serum CA19‐9 levels with the degree of impaired glucose regulation has also been reported.…”
Section: Introductionmentioning
confidence: 99%